Animal regeneration and microbial retention of nitrogen along coastal rocky shores. Issue 10 (1st October 2014) - Pfister, Catherine A.; Altabet, Mark A.; Post, David
Abstract : Animal contributions to ecosystem productivity via nutrient regeneration are increasingly recognized as significant for ecosystem productivity. The paradigm in coastal upwelling systems, in contrast, remains centered around the idea that nutrient supply is extrinsic and sourced from deep water. Here we tested for both animal contributions to nitrogen regeneration and microbial retention of nitrogen along a gradient of animal abundance in Washington State, USA. Using inferences from the concentration and isotopic composition of nitrogen forms, as well as the stable nitrogen isotopic composition of particulate organic matter, and plant and animal tissue, we found increased ammonium as well as greater stable nitrogen isotope values in these organisms in areas of increased animal abundance. We further tested the effect of the nearshore biota by comparing it with an immediately adjacent offshore area, and found an enriched δ 15 N value for nitrate and particulate organic matter. Further, an analysis of the dual isotopes of δ 15 N and the δ 18 O of nitrate indicated increasing microbial processing in the nearshore. Isoscapes, or the spatial pattern of stable isotopes, revealed that animal and microbial processing of nitrogen leave a consistent signature and are thus a previously overlooked and essential component of nearshore productivity.